2020
DOI: 10.1021/acs.orglett.0c03775
|View full text |Cite
|
Sign up to set email alerts
|

Pd(II)-Catalyzed Enantioselective Intramolecular Arylation of Unbiased C(sp3)–H Bonds to Construct Chiral Benzo-ring Compounds

Abstract: The asymmetric synthesis of chiral benzo-ring containing compounds through enantioselective intramolecular arylation of unbiased methylene C­(sp3)–H bonds was reported. Judicious choice of non-C2-symmetric chiral phosphoric acid (CPA) ligand is crucial for the high reactivity and enantioselectivity. The slight decrease in enantioselectivity at the late stage of the reaction was attributed to the hydrolysis of CPA ligands to the corresponding BINOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Based on this hypothesis, we developed non-C 2 -symmetric chiral phosphoric acids (CPAs) as first generation chiral ligands, 31 which enabled highly enantioselective inter-and intramolecular arylation of unbiased methylene C(sp 3 )−H bonds. 31,32 We further discovered a group of more readily accessible and widely applicable chiral ligands, namely, 3,3′-disubstituted BINOLs, which enabled a more divergently enantioselective functionalization of unbiased methylene C(sp 3 )−H bonds (Figure 8C). In our previously reported palladium-catalyzed PIP aminedirected arylation of methylene C(sp 3 )−H bonds, the addition of a catalytic amount of PivOH was found to significantly accelerate the reaction (Figure 6).…”
Section: Enantioselective Functionalization Ofmentioning
confidence: 85%
See 3 more Smart Citations
“…Based on this hypothesis, we developed non-C 2 -symmetric chiral phosphoric acids (CPAs) as first generation chiral ligands, 31 which enabled highly enantioselective inter-and intramolecular arylation of unbiased methylene C(sp 3 )−H bonds. 31,32 We further discovered a group of more readily accessible and widely applicable chiral ligands, namely, 3,3′-disubstituted BINOLs, which enabled a more divergently enantioselective functionalization of unbiased methylene C(sp 3 )−H bonds (Figure 8C). In our previously reported palladium-catalyzed PIP aminedirected arylation of methylene C(sp 3 )−H bonds, the addition of a catalytic amount of PivOH was found to significantly accelerate the reaction (Figure 6).…”
Section: Enantioselective Functionalization Ofmentioning
confidence: 85%
“…In a subsequent study, we successfully expanded this catalytic system into an intramolecular version, allowing the asymmetric synthesis of compounds containing chiral benzorings, such as chromanes and tetrahydroquinolines (Figure 10). 32 Fluorine-containing non-C 2 -symmetric CPAs (L1 and L2) gave the best yields and enantioselectivities. The evaluation of the time−yield and time−ee relationships revealed that the ee of the product slightly decreased in the late stages of this reaction (Figure 11A).…”
Section: Enantioselective Functionalization Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of chiral benzo-ring containing compounds were prepared using L43 as the chiral ligand (Scheme 31b). 68 In 2019, the Shi group developed a Pd(II)/3,3′-F 2 -BINOL-catalyzed enantioselective alkynylation of unbiased methylene C(sp 3 )-H bonds with alkynyl bromides directed by a PIP bidentate auxiliary. 69 of α-gem-dialkyl acyclic amides in 2020 (Scheme 31c).…”
Section: Desymmetric C(sp 3 )-H Functionalizationmentioning
confidence: 99%